The Role of Computer Media in The EFL Teachers’ Mindset on Teaching : A Narrative Inquiry - Fitria, Ifada Nur; Ariani, Musli; Setyono, Budi (EFL Education Journal, 2023)
The use of computer media by teachers for the benefit of teaching is something that is often encountered. With the character of open computer media, teachers can access all information. Of course, the information obtained will have the potential to influence the teacher's mindset or the teacher's perspective on something related to education. Therefore, this study aims to find out the roles of computer media in EFL teachers' mindset on teaching. This study used a narrative inquiry research design and used semi-structured interviews with two EFL teachers in Jember to obtain data. The data obtained was analyzed using thematic analysis and succeeded in finding the roles of computer media, including managing time, improving quality of instruction, encouraging active classes, controlling assignments, providing innovation, and tools for interaction. This study also found teachers' opinions about teaching EFL with and without computer media. It can be concluded that the roles of computer media facilitate the teaching of English. Therefore, the teacher assumes that computer media helps teachers in teaching and makes teachers more creative and varied when teaching.